Dovey coe - Dowell, Frances O'Roark (Walker Books London, 2002)
When accused of murder in her North Carolina mountain town in 1928, Dovey Coe, a stronged-willed twelve-year-old girl, comes to a new understanding of others, including her deaf brother. Suggested level: primary, intermediate, junior secondary